2015
DOI: 10.4174/astr.2015.88.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome for laparoscopic cholecystectomy in extremely elderly patients

Abstract: PurposeExtremely elderly patients who present with complicated gallstone disease are less likely to undergo definitive treatment. The use of laparoscopic cholecystectomy (LC) in older patients is complicated by comorbid conditions that are concomitant with advanced age and may increase postoperative complications and the frequency of conversion to open surgery. We aimed to evaluate the results of LC in patients (older than 80 years).MethodsWe retrospectively analyzed 302 patients who underwent LC for acute cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 27 publications
(46 reference statements)
1
46
0
2
Order By: Relevance
“…Preoperative cholecystostomy is useful procedure when the patient's condition is poor or the age is too old [19]. Although we excluded septic patient with cholecystitis, it is not uncommon clinical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative cholecystostomy is useful procedure when the patient's condition is poor or the age is too old [19]. Although we excluded septic patient with cholecystitis, it is not uncommon clinical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…There is no definitive view on the upper age limit for patients undergoing LC. The oldest patients were a 96-year-old reported by Lee et al[10] and a 102-year-old reported in China[45]. In our study, 112 patients underwent LC (including 7 patients who underwent LC + EST/EPBD)[46,47], with a success rate of 100%, and none of the patients were converted to laparotomy.…”
Section: Discussionmentioning
confidence: 77%
“…In particular, a subset of elderly patients may be at higher risk of developing postoperative complications and increased mortality due to the loss of physiological function and physical reserves[4,5]. Therefore, there is an unmet clinical need to characterize biliary diseases in elderly patients, in order to improve diagnosis and treatment for these diseases[6-10]. …”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] However, as many older patients present with conditions that increase surgery risk, or directly refuse surgical treatment, a conservative treatment sometimes has to be considered, which could lead to a prolonged hospital stay. Studies have demonstrated that early cholecystectomy is associated with shorter hospital stay, lower complication rates and reduced hospital spending.…”
Section: Discussionmentioning
confidence: 99%